Structural, optical and thermal properties of as-prepared and annealed gold-coated porous silicon - Behzad, Kasra (2012)
In this study, porous silicon (PSi) layers were prepared on n-type silicon (Si) substrates using the anodization method. Three sets of PSi samples were prepared under different current densities (10, 20, and 30 mA/cm2), where each set consisted of six samples that were prepared at different etching times (10, 20, 30, 40, 50, and 60 min). Gold was coated at different thicknesses (5, 10, and 20 nm) on PSi, Si, and glass substrates. Gold coated porous silicon (Au/PSi) with 20-nm thick gold layers, were selected for annealing at different temperatures (360, 600, 800, and 1000 °C). The structural characterizations were performed by gravimetrical method, Field Emission Scanning Electron Microscope (FESEM), and Energy Dispersive X-Ray Analyser (EDX). The porosity initially increased and then leveled off after attaining a certain value (47%–94%), but the thickness increased linearly with an increase in the etching time and current density (3.8–104 μm). For PSi samples, FESEM images showed that pores were formed on the surface. In the Au/PSi samples, a thin film of Au was coated on the porous structure. In the annealed Au/PSi samples, after annealing at a temperature higher than 360 °C, the surface of the samples were covered by silicon nanorods (SiNRs). The length of these nanorods varied between 110 and 1500 nm, and their diameter was tuned from 60 to 106 nm. Photoluminescence (PL) and photoacoustic spectroscopy (PAS) were carried out as optical characterizations. PL spectra show a peak for PSi and Au/PSi samples that is blue shifted towards higher energy, in the range of 700 to 600 nm, as the porosity is increased from 47% to 94%. The intensity of PL peaks raised around 50% by increasing the porosity and decreased (92 to 98%) by coating the gold layer (5 to 40 nm). The absorbance spectra achieved by PAS at modulation frequency of 73 Hz. It shows that the optical absorption raised by increasing the porosity. Gold deposition increased the absorbance and also pushed them up in the rangeof 500-800 nm. The band gap was calculated from PL and PA spectrum and the results are in good agreement with each other. The band gap increased linearly from 1.76 to 2.15 eV with porosity. Thermal characterization was fulfilled by PAS with chopping frequency, 20-240 Hz. The thermal diffusivity (TD) measured for PSi, Au/PSi and annealed Au/PSi samples. The TD reduced (0.33-0.08 cm2/s) with raising the porosity due to limitation of phonon mean free path. By gold deposition due to the additional metal layer, the TD increased to more than 25-38% of the PSi. After annealing the Au/PSi samples the TD decreased to the lowest value (0.23 to 0.27 cm2/s) at 360 oC. By growing the nanorods the TD increased (0.4 to 0.53 cm2/s) at 600 oC to the maximum value. It decreased (0.36 to 0.50 cm2/s) by increasing the annealing temperature to 800 and 1000 oC. Based on the first objective of dissertation; PSi samples were prepared, deposited and annealed under different conditions. By following the next three objectives, the structural, optical, and thermal investigations have been done on the samples to find the applicable applications for these samples. These investigations promote a novel field of study and can extend the applications of PSi as an interesting material in the nanotechnology and optoelectronics fields.